Spectrum of glomerular diseases in native kidneys in patients attending Nepal Medical College Teaching Hospital - Manandhar, D N; Chhetri, P K; Poudel, P; Singh, N; Baidya, S K; Maskey, A (Journal of Advances in Internal Medicine, 2017)
Background and Aims: Glomerular disease is the one of the major cause of end stage kidney disease in Nepal. We have undertaken this study to know the spectrum of glomerular disease in native kidneys in patients attending department of nephrology of Nepal Medical College Teaching Hospital. Methods: This is a retrospective analysis of patients who have undergone native kidney biopsy from July 2013 to June 2014. Seventy five cases were included. We reviewed the biopsy requisition and where available admission forms for symptoms, indications and complications of the biopsy, urine analysis report and final biopsy report. Kidney biopsy was done under USG guidance or assistance. Automated biopsy gun of 16 or 18G was used. Kidney tissues were sent for light microscopy and immune fluorescence examinations. After 24 hrs of biopsy, USG-KUB and urine RME were repeated for complications Results: Majority of our study population (62%) was from age group of 13 to 30 years. Sixty five percent of the patients (n= 49) were admitted with a diagnosis of nephrotic syndrome. Most frequent histopathological finding was Minimal Change Disease (26.7%) followed by LN (21.3%), Membranous Nephropathy (18.6%), Focal Segmental Glomerulosclerosis (13.4%) and IgA nephropathy (9.3%). Patients with the histopathological diagnosis of LN and IgAN presented with hematuria in 81.2% and 71.4% respectively. MCD patients presented with proteinuria only. Total no. of glomeruli in the sample was 23.41±11.55. Conclusion: Nephrotic syndrome was the most common indication for the renal biopsy. MCD was the most common histological finding in our series and Lupus nephritis is not uncommon in our series. Journal of Advances in Internal Medicine Vol.5(2) 2016: 24-28